Fully non-fused electron acceptor solar cells with 18% efficiency via a synergistic peripheral substituent strategy - Yeye Wang; Mingqun Yang; Zhili Chen; Jianbin Zhong; Feixiang Zhao; Wenkui Wei; Xiyue Yuan; Wei Zhang; Zaifei Ma; Zhicai He; Zhitian Liu; Fei Huang; et al. (Nature Communications)
Abstract Toward commercialization of organic solar cells (OSCs), photoactive materials that enable high efficiency yet possess low cost should be developed. Fully non-fused ring electron acceptors (FNEAs) that extend the conjugated skeleton with carbon–carbon (C–C) single bonds solely have lower synthetic costs than their fused-ring counterparts. However, the power conversion efficiencies (PCEs) of FNEAs are lagging due to low acceptor crystallinity and difficulty in the formation of fibrillary bi-continuous interpenetrating network morphology. Herein, we report four FNEAs (NEH-4F, EEH-4F, NBO-4F, and EBO-4F) through rational design of peripheral substituents. Specifically, the encapsulated central core guarantees the planarity of the conjugated skeleton and improves acceptor crystallinity, while the lengthened outer side chains modulate the molecular stacking and regulate the thermodynamic compatibility between the FNEAs and the polymer donor PTTz. Therefore, nanoscale phase separation morphology with bi-continuous interpenetrating fibril network structures was found in the blend of PTTz:EBO-4F, which promotes exciton diffusion and charge transport in solar cells. A record-breaking PCE of 18.04% is thus obtained, which greatly reduces the efficiency gap between FNEAs and fused-ring electron acceptors. These results demonstrate the promising prospect of fabricating high-efficiency OSCs from low-cost FNEAs through rational molecular design.